Rwanda : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper analyzes investment strategy to foster structural transformation in Rwanda. Over the past 15 years, Rwanda has transformed its economy by moving workers out of agriculture into mostly services and some industry. This has been accomplished through strong public investment flows and efficient public investment management. Going forward, the challenge is whether the private sector can complement the infrastructure assets put in place by the public sector and maintain economic momentum. It will also require continued effort by the government in raising education standards, better matching qualifications offered to students to those most in demand by employers, and lowering electricity and transportation costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economics of Gender; Non-Labor Discrimination